Livestock grazing limits beaver restoration in northern New Mexico. Issue 5 (11th May 2016) - Small, Brian A.; Frey, Jennifer K.; Gard, Charlotte C.
Abstract : The North American beaver ( Castor canadensis ) builds dams that pond water on streams, which provide crucial ecological services to aquatic and riparian ecosystems and enhance biodiversity. Consequently, there is increasing interest in restoring beavers to locations where they historically occurred, particularly in the arid western United States. However, despite often intensive efforts to reintroduce beavers into areas where they were severely reduced in numbers or eliminated due to overharvesting in the eighteenth and nineteenth centuries, beavers remain sparse or missing from many stream reaches. Reasons for this failure have not been well studied. Our goal was to evaluate certain biotic factors that may limit the occurrence of dam‐building beavers in northern New Mexico, including competitors and availability of summer and winter forage. We compared these factors at primary active dams and at control sites located in stream reaches that were physically suitable for dam‐building beavers but where none occurred. Beaver dams mostly occurred at sites that were not grazed or where there was some alternative grazing management, but were mostly absent at sites within Forest Service cattle allotments. Results indicated that cattle grazing influenced the relation between vegetation variables and beaver presence. The availability of willows ( Salix spp.) was the most important plant variable for the presence of beaver dams. We conclude that grazing by cattle as currently practiced on Forest Service allotments disrupts the beaver‐willow mutualism, rendering stream reaches unsuitable for dam‐building beavers. We recommend that beaver restoration will require changes to current livestock management practices.